THE EFFECTIVENESS OF SCRAMBLE LEARNING MODEL ON STUDENTS MATHEMATICS LEARNING OUTCOMES IN CLASS VII - Iryana Setyaningrum; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2020)
SMP Muhammadiyah 1 Minggir is one of the schools whose learning result of mathematics is still low. The learning process used is still teacher-centered and less varied. This makes the student's lack of attention to the teacher's explanations in the classroom learning. One of the learning models that focuses students' attention on teacher explanation is the Scramble learning model. The purpose of this study to determine the effectiveness of learning models between students who use the Scramble learning model to students in class VII odd semester junior high school (SMP) of Muhammadiyah 1 Minggir Sleman District Academic Year 2019/2020. This study population is the seven graders of junior high school Muhammadiyah 1 Minggir Sleman District Academic Year 2019/2020, which consists of seven classes. The technique of sampling research used a random sampling technique that is by lottery. The classes obtained are class VII B as the experimental class using the Scramble learning model and VII C as the control class using the direct learning model. Methods of data collection using the method of documentation of students' initial ability and test. Research instruments consisting of interviews with teachers and students, observations, and multichoice mathematical test results. Data analysis used is a prerequisite analysis test consisting of normality test and homogeneity test, then a hypothesis test using t-test the first hypothesis and t-test the second hypothesis. The significant level of 5% and DF = 62 show that: (1) there are differences in students mathematics learning outcomes using Scramble and mathematics learning outcomes of students who use direct learning. This was evidenced by the value of tcount = and ttable = , so that tcount > ttable means rejecting H0. (2) Mathematic learning of students who used the Scramble learning model was more effective than students who used direct learning on mathematics learning outcomes. The value of tcount =  evidenced this and ttable = , so that tcount > ttable means that rejecting H0.